Applying Consumer Behavior Theory integrated with Supply Chain Strategy in the Context of the Digital Transformation of the Economy - A.Yegina, Natalya; S.Zemskova, Elena; A.Gorin, Vladimir; I.Stepanova, Diana (International Journal of Supply Chain Management, 2019)
The article deals with the study of the consumer behavior by considering the supply chain strategy in the context of a rapid digital transformation. The urgency and significance of the identified problem for science and practice are stipulated, on the one hand, by objective economic laws and major trends of the modern era, and on the other, by the problems of developing a model of the digital consumer’s responsible behavior.The purpose of this research is the development of ideas about factors (determinants) influencing consumer behavior in the context of digital transformation, which at present is acquiring not only a socio-economic, but also a considerable ethical significance.The theoretical and methodological principles of the systemic and interdisciplinary approaches allowed us to identify two main groups of consumer behavior models: the conservative “homo economicus” model and models based on T. Veblen’sideas adapted to the socio-economic reality of the 20th-21 st centuries. The capabilities of the modern digital economy make full use of consumer effects described by Veblen and not just “nudge” the consumer to make the targeted decision, but form a new type of consumers online, who are integrated into various communities and do not have information barriers.